Implementation of Digital-Based Fiqh Learning with Direct Instruction and Teams Games Tournament: Implementasi Pembelajaran Fiqh Berbasis Digital dengan Metode Pengajaran Langsung dan Turnamen Permainan Tim - Fatih Alwi Haya Lubis; Ihsan Satrya Azhar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Learning Islamic jurisprudence (fiqh) often encounters challenges such as low student interest and participation, as well as teachers’ difficulties in delivering conceptual material. Specific Background: These conditions underscore the need for innovation through digital-based learning approaches. Knowledge Gap: Previous studies have seldom examined the comprehensive integration of digital media in fiqh learning. Aims: This study aims to explore the implementation of digital-based fiqh learning, focusing on the aspects of planning, implementation, and evaluation. Results: Employing a descriptive qualitative method through observation, interviews, and documentation, the findings indicate that teachers utilized digital media such as PowerPoint, YouTube, and Google Drive, supported by Direct Instruction and Teams Games Tournament (TGT) models. This approach increased student engagement, improved material comprehension, and fostered 21st-century skills, although challenges persisted with network reliability and uneven digital competence. Novelty: The study highlights the effectiveness of combining the TGT model with digital media in fiqh learning. Implications: These findings provide practical contributions to developing more engaging, interactive, and contextually relevant fiqh learning strategies in the digital era. Highlights: Digital media enhances engagement and understanding in fiqh learning. TGT and Direct Instruction models effectively support digital integration. Challenges remain in digital competence and network stability. Keywords: Digital Learning, Fiqh Education, Direct Instruction, Teams Games Tournament, Student Engagement